THE PERCEPTIONS OF COMMUNITY MEMBERS REGARDING THE ROLE OF SOCIAL WORKERS IN ENHANCING SOCIAL CAPITAL IN METROPOLITAN AREAS TO MANAGE HIV AND AIDS - Sesane, Malebo; Geyer, Stephan (Social Work/Maatskaplike Werk, 2017)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Social welfare policies mandate social workers to build social capital in order to, amongst other things, manage the impact of HIV and AIDS on communities. However, the views of community members residing in metropolitan areas about the roles that social worker could perform in enhancing social capital to manage HIV and AIDS are inadequately described. One comprehensive focus group discussion was conducted with 10 community members representing four NPOs involved in HIV and AIDS work across the Johannesburg and Ekurhuleni Metros. Recommendations are made to social workers to enhance social capital, and guidelines and strategies offered to fulfil this obligation through developmental social work.